Developing a school-community health program within the context of primary health care an alternative approach - Fontanilla, Ma. Alodia C. (Education quarterly.)
This study was undertaken to develop a comprehensive school community health program integrating health instruction, health services, healthful school living and school-community coordination within the context of primary health care for a more effective health education of children and youth so that they will mature into responsible, productive and happy members of society. The findings of the study were: student's health needs and interests are varied; the teacher are competent only in the aspect of health instruction; the parents believe that the teachers are doing all the functions except for one; the barangay leaders perceive the teachers to be doing only half of the health teacher functions ...